Advancing Marine Biogeochemical and Ecosystem Reanalyses and Forecasts as Tools for Monitoring and Managing Ecosystem Health - Fennel, Katja; Gehlen, Marion; Brasseur, Pierre; Brown, Christopher W.; Ciavatta, Stefano; Cossarini, Gianpiero; Crise, Alessandro; Edwards, Christopher A.; Ford, David; Friedrichs, Marjorie A. M.; Gregoire, Marilaure; Jones, Emlyn; et al. (Frontiers in Marine Science, 2019)
Ocean ecosystems are subject to a multitude of stressors including changes in ocean physics and biogeochemistry, and direct anthropogenic influences. Implementation of protective and adaptive measures for ocean ecosystems requires a combination of ocean observations with analysis and prediction tools. These can guide assessments of the current state, elucidate ongoing trends and shifts, and anticipate impacts of climate change and management policies. Analysis and prediction tools are defined here as ocean circulation models that are coupled to biogeochemical or ecological models. The range of potential applications for these systems is broad from reanalyses for assessment of past and current states, and short-term and seasonal forecasts, to scenario simulations including climate change projections. The objectives of this article are to illustrate current capabilities with regard to the three types of applications and to discuss challenges and opportunities. Representative examples of global and regional systems are described with particular emphasis on those in operational or pre-operation use. With regard to benefits and challenges, similar considerations apply to biogeochemical and ecological prediction systems as do to physical systems. However, at present there are at least two major differences: 1) biogeochemical observations streams are much sparser than physical streams presenting a significant hinderance, and 2) biogeochemical and ecological models are largely unconstrained because of insufficient observations. Expansion of biogeochemical and ecological observing systems will allow for significant advances in the development and application of analysis and prediction tools for ocean biogeochemistry and ecosystems with multiple societal benefits.